2006
DOI: 10.1111/j.1526-4610.2006.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Premenstrual Syndrome and Their Association With Migraine Headache

Abstract: Moderate correlations exist within female migraineurs between the severity of PMS symptoms and headache outcome measures throughout natural menstrual cycles as well as after medical oophorectomy. Our data would suggest that the presence and severity of headache might modulate PMS symptoms in female migraineurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 17 publications
2
15
0
1
Order By: Relevance
“…Martin et al [23] undertook a 6.5-month randomized, controlled trial to examine the role of medical oophorectomy in the prevention of migraine headache. Each of three native menstrual cycles was subdivided into seven 3-day intervals based on urine hormone metabolites.…”
Section: Premenstrual Syndromementioning
confidence: 99%
“…Martin et al [23] undertook a 6.5-month randomized, controlled trial to examine the role of medical oophorectomy in the prevention of migraine headache. Each of three native menstrual cycles was subdivided into seven 3-day intervals based on urine hormone metabolites.…”
Section: Premenstrual Syndromementioning
confidence: 99%
“…Several mechanisms have been used to explain why the decline in estrogen may cause migraine headaches. These mechanisms include abnormal platelet aggregation, impaired regulation of opioids on the central nervous system and stimulating increased production of prostaglandins in the central nervous system [14,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…PMS associated with menstrual migraine has been evaluated and increased symptoms of PMS associated with menstrual migraine were observed [18][19][20][21][22][23][24][25]. It is therefore suggested that all women with PMS be examined for the presence of menstrual migraine using IHS criteria (International headache society) as medical and social consequences of menstrual headache affect not only the women but also their family [25].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Hutchinson and colleagues [30] reported that women suffering from migraine also frequently observe headache during PMS. Most recently, Martin et al [31] found that premenstrual symptoms were more severe when patients were experiencing migraine. The association between these pain syndromes and PMS is consistent with the hypothesis that these syndromes maybe linked to fluctuations in the levels of estrogen and progesterone [32].…”
Section: Discussionmentioning
confidence: 99%